PELATIHAN PEMASARAN PRODUK BUMDesa BERBASIS DIGITAL DI KABUPATEN BENGKALIS - Nur Azlina; Desmiyawati Desmiyawati; Al Azhar A; Suci Nurulita; Sinta Ramaiyanti; Fitri Humairoh; Taqiyuddin Amri (Unri Conference Series: Community Engagement, 2021)
This community service activity was carried out at the BUMDesa, Bengkalis District. The purpose of this community service activity is to 1) increase knowledge of the importance of the digital world for the development of BUMDesa, 2) encourage BUMDesa players to digitize the products offered, 3) introduce new marketing methods for BUMDesa players through the marketplace. The benefits of this community service activity are to increase the knowledge and ability of BUMDesa actors in utilizing digital technology in marketing BUMDesa product. The target audience for this activity are BUMDesa actors in the Bengkalis sub-district. The method used in community service activities is to use training methods for several BUMDesa in Bengkalis District. After the training activities have been carried out, the implementing team will follow up by forming a mentoring and coaching group for BUMDesa. The purpose of this follow-up is done offline and online using the zoom application, google meet, or can be via whatsapp. The purpose of holding a follow-up is to see the knowledge of BUMDesa and existing obstacles so that if there are obstacles, they can be handled immediately.